Antibacterial activity of a new broad‐spectrum antibiotic covalently bound to titanium surfaces. Issue 12 (6th April 2016) - Gerits, Evelien; Kucharíková, Soňa; Van Dijck, Patrick; Erdtmann, Martin; Krona, Annika; Lövenklev, Maria; Fröhlich, Mirjam; Dovgan, Barbara; Impellizzeri, Frédéric; Braem, Annabel; Vleugels, Jef; Robijns, Stijn C. A.; et al.
ABSTRACT: Biofilm‐associated infections, particularly those caused by Staphylococcus aureus, are a major cause of implant failure. Covalent coupling of broad‐spectrum antimicrobials to implants is a promising approach to reduce the risk of infections. In this study, we developed titanium substrates on which the recently discovered antibacterial agent SPI031, a N‐alkylated 3, 6‐dihalogenocarbazol 1‐(sec‐butylamino)‐3‐(3, 6‐dichloro‐9H‐carbazol‐9‐yl)propan‐2‐ol, was covalently linked (SPI031‐Ti). We found that SPI031‐Ti substrates prevent biofilm formation of S . aureus and Pseudomonas aeruginosa in vitro, as quantified by plate counting and fluorescence microscopy. To test the effectiveness of SPI031‐Ti substrates in vivo, we used an adapted in vivo biomaterial‐associated infection model in mice in which SPI031‐Ti substrates were implanted subcutaneously and subsequently inoculated with S. aureus . Using this model, we found a significant reduction in biofilm formation (up to 98%) on SPI031‐Ti substrates compared to control substrates. Finally, we demonstrated that the functionalization of the titanium surfaces with SPI031 did not influence the adhesion and proliferation of human cells important for osseointegration and bone repair. In conclusion, these data demonstrate the clinical potential of SPI031 to be used as an antibacterial coating for implants, thereby reducing the incidence of implant‐associated infections. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:2191–2198, 2016.